Recommendations for a safety dental care management during SARS-CoV-2 pandemic - Paulo Ricardo Martins-Filho; Vanessa Tavares de Gois-Santos; Carolina Santos Souza Tavares; Elisama Gomes Magalhães de Melo; Edmundo Marques do Nascimento-Júnior; Victor Santana Santos (Pan American Health Organization, 2020)
As the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is transmitted mainly through droplets, sneezes and aerosols, there is a high risk of transmission during dental procedures. This report describes measures that can be adopted by oral healthcare personnel to minimize the risk of cross-contamination in clinical practice during the current SARS-CoV-2 pandemic.